2012
DOI: 10.1177/0165025412446394
|View full text |Cite
|
Sign up to set email alerts
|

The relationships among language ability, emotion regulation and social competence in second-grade students

Abstract: Relationships exist between language ability, emotion regulation, and social competence in preschool children. This study examines how these relationships function in elementary school children, and explores whether language ability partially mediates the relationship between emotion regulation and social competence. Second-grade students (N ¼ 67) completed an assessment of receptive vocabulary, and teachers rated emotional and social skills. Results show relationships between emotion regulation and social com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 41 publications
1
25
1
1
Order By: Relevance
“…The BASC-2 and its previous edition (e.g. BASC-1) have been found to be reliable and valid (Monopoli & Kingston, 2012;Sandoval & Echandia, 1994). It has also been found suitable with immigrant children from Chinese families (Zhou et al, 2003) and children in Australia (Baker & Jones, 2006).…”
Section: Social Competencementioning
confidence: 97%
See 1 more Smart Citation
“…The BASC-2 and its previous edition (e.g. BASC-1) have been found to be reliable and valid (Monopoli & Kingston, 2012;Sandoval & Echandia, 1994). It has also been found suitable with immigrant children from Chinese families (Zhou et al, 2003) and children in Australia (Baker & Jones, 2006).…”
Section: Social Competencementioning
confidence: 97%
“…Inconsistencies between China and Western societies in language, behaviours, beliefs, social practices and physical appearance may compromise these children's abilities to develop social competence. Social competence refers to a child's abilities to respond flexibly to social challenges and is found to be associated with cognitive and academic development (Monopoli & Kingston, 2012;Semrud-Clikeman, 2007). Helping immigrant children develop social competence to integrate with the larger society and stay happy and healthy should be the important goals for the receiving countries to fulfil (Beiser et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For the second micro-trial, the literature has shown that a higher level of EB is frequently associated with poor communication skills (Gallagher, 1999;Monopoli & Kingston, 2012;Van Schendel, Schelstraete, & Roskam, 2013). First, poor communication skills can cause behavioral problems, as difficulties in both understanding and producing verbal responses appropriate to the social context may lead to non-compliance and aggressiveness (Kaiser, Hancock, Cai, Foster, & Hester, 2000).…”
mentioning
confidence: 99%
“…Several variables have been shown to contribute to this increase in prosocial behavior, e.g., verbal abilities, executive functions in general as well as emotion regulation (e.g., Cassidy et al, 2003; Cole et al, 2010; Ensor et al, 2011; Miyake and Friedman, 2012; Monopoli and Kingston, 2012; for an overview see Decety, 2010). The fact that the quantity of children's helping behavior increases with age might also be attributed to specific aspects of socioemotional development.…”
Section: Introductionmentioning
confidence: 99%